(3GdehLR aj GdfMhs - (3CHhHcQ eMeO Hf GdSQj Hf Sgd GdeYQha HGHf GdSQGL,J (B316 (3g` s
(3ChdgG (B:s
(3GdcdGe jCJda ef KdGKI CTjGA, GSe haYd hMQa aGdGSe eG LGR Cf JNHQ Yfg fMh YeQh s
(3BNQgG (B:s
(3hcPdc GdZjf hGdNGA, Jbhd UGFZ aj SGdZ, hUdN aj SdN, hUGWY aj SGWY Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HChdgG JGQjN (B559(3g` hCfgG YhQVJ HGdagQS SfI (B581(3g`s
(3hgj fSNI cJHJ Yf fSNI ebQhAI Ydi CMO CUMGH GdeUfa hHgG fXGe GdJYbjHI hHBNQgG ebOGQ UaMI aj (B"(3Gdbde(B" (3ddeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B174 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B318 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B899s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs